Frente de Aragon. Members of the 26th Division (Columna Durruti) waiting for a letter from home and writing. Series of 2 photos. Copied from CNT collection
Frente de Aragon. Members of the 26th Division (Columna Durruti) waiting for a letter from home and writing. Series of 2 photos. Copied from CNT collection.